The Novelist as a Historian: A Study of the Nigerian/Biafran War Account from the Perspective of Chukwuemeka Ikeh’s Sunset at Dawn - Obuasi, Ifeoma; OZOEMENA, JOHNKENEDY AZUBUIKE; Ugwuagbo, Walter Osondu (International Journal of Language and Literary Studies, 2022)
The novelist is a creator and a creative writer whose foundation is lodged in imaginative thinking. It is in the creative writer’s ability to recreate events, which had either taken place or could take place, through the use of fictive characters, and creative use of language. This study therefore introspects the events of the Nigerian/Biafra civil war from the perspective of the novelist as a historian, in doing this the study examines the events of the civil war from the literary perspectives and accounts of a literary giant Chukwu Emeka Ikeh’s Sunset at Dawn. Data for the study is collected from secondary sources, the text under study and other Nigerian/Biafran war novels, historical books about the civil war, and internet sources. The study adopted the theory of historicism as a frame work. It highlighted the civil war era from the perspective of the writer under study, from the beginning of the conflict to when it became a full-blown war, the killings, starvation, hunger and the end of the war. The study identified some of the remote causes of the war to be the fear of political domination among the three major ethnic groups in Nigeria, deep seated ethnic resentment and acrimony among others. This study recommends that similar situation in future can only be averted through power devolution, all- inclusive leadership style and equitable distribution of the nation’s resources.